3,4 : 5,6-di-O-isopropylidene-3-C-hydroxy-methyl-D-altrono-1,3 '-lactone - Parker, S; Watkin, D; Simone, M; Fleet, G (2006)
The title compound, C13H20O7, a rare example of a sugar with a carbon branch at C-3, is one of the major products isolated from the treatment of D-hamamelose with cyanide (the Kiliani reaction), followed by protection as a diacetonide. The material crystallizes with two molecules in the asymmetric unit, related to each other by a non-crystallographic twofold axis. © 2006 International Union of Crystallography. All rights reserved.